Jaap Kunst Legacies: A Site of Forgetting, Remembering and History-Making - Aryandari, Citra (Resital: Jurnal Seni Pertunjukan, 2022)
ABSTRACT The study interrogate and reconfigure the project of disclosing the heritage of ethnomusicologist Jaap Kunst. Jaap Kunst recorded a lot of Indonesian music while living in Indonesia from 1919-1934. The teaching material and the development of ethnomusicology concepts as knowledge based on the sound record and his research experience. Now, after nearly 100 years, the Musicology Department of University van Amsterdam is initiating the opening of the Jaap Kunst legacy that has not yet been published. Because this heritage is related to Indonesia's cultural history and memory, University van Amsterdam collaborates with academics from Indonesia and trying to find support from the Indonesian government.   This study introduces philosophical approaches to reflection: critical, hermeneutic, and finally phenomenological. Reveal the dynamic relationship between Jaap Kunst legacies as a historical artifact and a site of forgetting, remembering, and history-making. How were the memory and identity stored in the Jaap Kunst materials reinterpreted in the postcolonial era? How is ethnomusicology addressing this matter related to shaping the colonial knowledge into the various subject positions? This paper is discussed with a retrospective approach in which individuals are sampled and information is collected about their past. Through interviews in some participants are asked to recall important events, or by identifying relevant administrative data to fill in information on past events and circumstances. With that method I assumed that tracking down Kunst's legacy was like taking a vacation at grandma's house, bringing back all the memories but not necessarily related to the present.  ABSTRAK Tulisan ini menginterogasi dan mengonfigurasi ulang proyek pembukaan warisan etnomusikolog yang Bernama Jaap Kunst. Jaap Kunst merekam banyak musik Indonesia selama tinggal di Indonesia dari tahun 1919-1934 dan menjadikan sebagai bahan ajar serta pengembangan konsep etnomusikologi sebagai ilmu pengetahuan berdasar rekaman suara dan pengalaman penelitiannya. Kini, setelah hampir 100 tahun, Departemen Musikologi Universitas Amsterdam memprakarsai pembukaan warisan Jaap Kunst yang belum sempat dipublikasikan. Warisan ini terkait dengan sejarah dan ingatan budaya Indonesia, Universitas Van Amsterdam bekerja sama dengan akademisi dari Indonesia dan berusaha mencari dukungan dari pemerintah Indonesia. Tulisan ini memperkenalkan pendekatan filosofis untuk refleksi: kritis, hermeneutik, serta fenomenologis. Mengungkapkan hubungan dinamis antara warisan Jaap Kunst sebagai artefak sejarah dan situs melupakan, mengingat, dan membuat sejarah. Bagaimana ingatan dan identitas yang tersimpan dalam materi Jaap Kunst diinterpretasikan ulang di era pascakolonial? Bagaimana etnomusikologi menyikapi hal ini terkait dengan pembentukan pengetahuan kolonial ke dalam berbagai posisi subjek? Pembahasan dalam tulisan ini menggunakan pendekatan retrospektif di mana individu diambil sampelnya dan dikumpulkan informasi tentang masa lalunya. Melalui wawancara beberapa partisipan diminta untuk mengingat kembali peristiwa-peristiwa penting, atau dengan mengidentifikasi data administrasi yang relevan untuk mengisi informasi tentang peristiwa dan keadaan masa lalu. Dengan cara itu dapat diasumsikan menelusuri peninggalan Kunst  seperti berlibur ke rumah nenek, membawa kembali semua kenangan tapi tidak harus terkait dengan masa kini.